The Effects of the Synectics Teaching Model Combined with the EKKE Model to Promote Creative Writing of Sixth Primary Students - Supithak, Sumitta; Chomchuen, Alisara; Udomphan, Cherdchai (Journal of Buddhist Psychology, 2024)
The purposes of this research were 1) to compare the creative writing skills of sixth-grade students before and after using the Synectics teaching model combined with the EKKE model and 2) to study students’ satisfaction with the teaching. The research was the quasi-experimental design, one group pretest-posttest design. The samples were 30 sixth-grade students from Banbophut School, Suratthani, in the Primary Education Service Area Office 1. The instruments were 1) 5 lesson plans with the Synectics teaching model combined with the EKKE model, 2) a creative writing skills test, and 3) a satisfaction questionnaire of the Synectics teaching model combined with the EKKE model. The statistics used include mean and dependent t-test. The research findings were as follows: 1) The mean of students’ creative writing skills earlier teaching was 12.13, and the after teaching was 21.37. As a result, the creative writing skills were significantly higher than before teaching at the level of .01. 2) Overall, the result of students’ satisfaction by using the teaching model was at a high level, with a mean of 3.59 and a standard deviation of .36. The highest level of satisfaction was that students were content with their studies; the mean was 4.20 and the standard deviation was .96.